The use of locum doctors in the NHS – results of a national survey of NHS Trusts in England - Stringer, Gemma; Ferguson, Jane; Walshe, Kieran; Grigoroglou, Christos; Allen, Thomas; Kontopantelis, Evangelos; Ashcroft, Darren M. (BMC health services research, 2023)
Background Locum working in healthcare organisations has benefits for individual doctors and organisations but there are concerns about the impact of locum working on continuity of care, patient safety, team function and cost. We conducted a national survey of NHS Trusts in England to explore locum work, and better understand why and where locum doctors were needed; how locum doctors were engaged, supported, perceived and managed; and any changes being made in the way locums are used. Methods An online survey was sent to 191 NHS Trusts and 98 were returned (51%) including 66 (67%) acute hospitals, 26 (27%) mental health and six (6%) community health providers. Data was analysed using frequency tables, t-tests and correlations. Free-text responses were analysed using thematic analysis. Results Most NHS Trusts use locums frequently and for varying lengths of time. Trusts prefer to use locums from internal locum banks but frequently rely on locum agencies. The benefits of using locums included maintaining workforce capacity and flexibility. Importantly, care provided by locums was generally viewed as the same or somewhat worse when compared to care provided by permanent doctors. The main disadvantages of using locum agencies included cost, lack of familiarity and impact on organisational development. Some respondents felt that locums could be unreliable and less likely to be invested in quality improvement. NHS Trusts were broadly unfamiliar with the national guidance from NHS England for supporting locums and there was a focus on processes like compliance checks and induction, with less focus on providing feedback and support for appraisal. Conclusions Locum doctors provide a necessary service within NHS Trusts to maintain workforce capacity and provide patient care. There are potential issues related to the way that locums are perceived, utilised, and supported which might impact the quality of the care that they provide. Future research should consider the arrangements for locum working and the performance of locums and permanent doctors, investigating the organisation of locums in order to achieve safe and high-quality care for patients.